2023
DOI: 10.26599/jac.2023.9220798
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of SiC coated graphite composite powders by nitriding combustion synthesis

Biao Zhang,
Wenqi Xie,
Huaizhi Lin
et al.

Abstract: Ceramic-coated graphite powders are considered as effective raw materials to fabricate three-dimensional continuous ceramic skeleton-reinforced graphite matrix composites which can overcome their inherent poor densification and improve their mechanical and antioxidation properties. However, the morphology and thickness regulation of ceramic coatings on graphite particles are still a great challenge. Herein, SiC-coated graphite (graphite@SiC) powders were prepared by nitriding combustion synthesis using Si and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 69 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…The TC value in the x – y plane first increased from 277 W/m/K for the GF@4SiC composite to 322 W/m/K for the GF@9SiC composite and then decreased to 223 W/m/K for the GF@27SiC composite. Previous studies have shown that the TC of composites is significantly influenced by pores, defects, and interfaces 32–34 . With an increase in the SiC volume fraction, an increase in the number of interfaces leads to a reduction in the TC of the GF@SiC composites.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The TC value in the x – y plane first increased from 277 W/m/K for the GF@4SiC composite to 322 W/m/K for the GF@9SiC composite and then decreased to 223 W/m/K for the GF@27SiC composite. Previous studies have shown that the TC of composites is significantly influenced by pores, defects, and interfaces 32–34 . With an increase in the SiC volume fraction, an increase in the number of interfaces leads to a reduction in the TC of the GF@SiC composites.…”
Section: Resultsmentioning
confidence: 98%
“…and interfaces. [32][33][34] With an increase in the SiC volume fraction, an increase in the number of interfaces leads to a reduction in the TC of the GF@SiC composites. However, our study showed that the density of the GF@SiC composites increased and the porosity decreased as the SiC content increased from 4 to 9 vol.%, resulting in an improvement in the TC of the composites.…”
Section: Thermophysical Properties Of Gf@sic Compositesmentioning
confidence: 99%